Pertimbangan Hukum Hakim Terhadap Anak Kekerasan Fisik Dalam Rumah Tangga (Putusan Nomor: 326/Pid.Sus/2019/PN.Amb) - Regina Latuheru; Margie Gladies Sopacua; Astuti Nur Fadillah (PATTIMURA Law Study Review, 2023)
ABSTRACT: Children who experience criminal acts of physical violence are very vulnerable to mental and psychological shocks. Legal assistance and protection of children who are victims of criminal acts is the duty and responsibility of parents and the surrounding environment, but in some cases parents commit violence against the children themselves so that they must accept the consequences in the form of imprisonment in accordance with the judge's decision through his consideration. The purpose of this research is intended to obtain clarity and legal certainty by identifying and analyzing"Judges’s Legal Considerations Against Children of Domestic Physical Violence (Decision Number: 326/Pid.Sus/2019/PN.Amb)". The purpose and protection of children based on the Child Protection Law is to ensure the fulfillment of children's rights so that they can live, grow, develop, and participate optimally in accordance with human dignity, and receive protection from violence and discrimination for the realization of quality Indonesian children. The research in this thesis makes positive legal norms and doctrines using a statutory approach (statue approach) to find out the problem solving and the resulting solution. Legal protection if you look at the judge's consideration in the court decision, fulfills the consideration of juridical elements. The form is that the judge says that the defendant's actions fulfill the elements so that the judge imposes a penalty. Before convicting the perpetrator, the judge proves the fulfillment of the criminal elements. The legal protection provided to victims in the court decisions that the author examines, where the judge convicts the perpetrator and states the fulfillment of the criminal elements. The conclusion of this legal writing is that parents, society and the government take part in the legal protection of children and also provide a deterrent effect to perpetrators who commit criminal acts of violence against children.